Thomas Aquinas on Abstinence and Fasting: Participating in Christ's Cruciform Wisdom. Issue 4 (November 2019) - O'Reilly, Kevin E.
This article argues that St. Thomas Aquinas's treatise on temperance in the Summa Theologiae offers what in effect constitutes a series of embodied spiritual exercises whose goal is to facilitate the reader in his progress towards the contemplation of Divine realities. Attention to Thomas's treatment of Christ's Passion reveals moreover that the embodied wisdom practices of abstinence and fasting lead to a greater participation in the Cross of Christ and prepare the one who undertakes them for the reception of a cruciform wisdom. Finally, it is argued, these embodied wisdom practices also exert an influence on the pursuit of speculative theological wisdom.